The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/su122310209
|View full text |Cite
|
Sign up to set email alerts
|

Visual Literacy Intervention for Improving Undergraduate Student Critical Thinking of Global Sustainability Issues

Abstract: The promotion of global sustainability within environmental science courses requires a paradigm switch from knowledge-based teaching to teaching that stimulates higher-order cognitive skills. Non-major undergraduate science courses, such as environmental science, promote critical thinking in students in order to improve the uptake of scientific information and develop the rational decision making used to make more informed decisions. Science, engineering, technology and mathematics (STEM) courses rely extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Moreover, following the present results, previous studies have demonstrated that difficulties in achieving sustainable educational institutions continue to be presented [92], and these organizations should move towards sustainable goals [93]. Nevertheless, most studies focused on the students as the most significant agents, integrating the new educational models accordingly o their age [14,73,94]. Despite that, Freidenfelds et al [92] indicated that sustainable goals should focus on the stakeholders, students, researchers, and staff, being optimal to understand the teachers better.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, following the present results, previous studies have demonstrated that difficulties in achieving sustainable educational institutions continue to be presented [92], and these organizations should move towards sustainable goals [93]. Nevertheless, most studies focused on the students as the most significant agents, integrating the new educational models accordingly o their age [14,73,94]. Despite that, Freidenfelds et al [92] indicated that sustainable goals should focus on the stakeholders, students, researchers, and staff, being optimal to understand the teachers better.…”
Section: Discussionsupporting
confidence: 69%
“…Universities have established student mental health management institutions such as mental health counseling centers and mental health consultation centers, aiming to care for students' mental health seriously, carefully counsel them on their psychological problems, scientifically diagnose their psychological diseases, and avoid the occurrence of their psychological problem crises [5][6]. Its main form is to map students' mental health problems, identify problems, and initiate psychological education classes such as lectures, mainly by distributing mental health questionnaires and analyzing them statistically [7][8][9]. When students encounter psychological problems, they take the initiative to visit the counseling room and communicate face-to-face with the counselor [10].…”
Section: Background Of the Studymentioning
confidence: 99%
“…This is because scientific literacy is one of the basic life skills that must be mastered by 21st-century society. Scientific literacy is importantly used to solve various problems related to science and technology (Krejci et al, 2020;Yaacob & Lubis, 2022). The 2013 curriculum states that education should not separate students from their environment so that development is based on educational principles that are relevant to the needs and environment of students.…”
Section: Introductionmentioning
confidence: 99%